2010
DOI: 10.1073/pnas.0914805107
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin 1A receptor gene as a genetic and prenatal maternal environmental factor in anxiety

Abstract: Low serotonin 1A receptor (5-HT 1A R) binding is a risk factor for anxiety and depression, and deletion of the 5-HT 1A R results in anxiety-like behavior in mice. Here we show that anxiety-like behavior in mice also can be caused, independently of the offspring's own 5-HT 1A R genotype, by a receptor deficit in the mother: a nongenetic transmission of a genetic defect. Some of the nongenetically transmitted anxiety manifestations were acquired prenatally and linked to a delay in dentate gyrus maturation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 38 publications
5
75
0
Order By: Relevance
“…Recent studies related to mood and anxiety have indicated that genetic factors may also influence neurodevelopment by altering maternal physiology during pregnancy (Toth, 2014). Interestingly, maternal genotype effects on fetal development have been reported in offspring of 5-HT 1A and TPH1 null mice (Cote et al, 2007;Gleason et al, 2010). Although very useful for understanding these components of the 5-HT system, complete loss of these critical proteins does not occur in the human population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies related to mood and anxiety have indicated that genetic factors may also influence neurodevelopment by altering maternal physiology during pregnancy (Toth, 2014). Interestingly, maternal genotype effects on fetal development have been reported in offspring of 5-HT 1A and TPH1 null mice (Cote et al, 2007;Gleason et al, 2010). Although very useful for understanding these components of the 5-HT system, complete loss of these critical proteins does not occur in the human population.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence points to maternal genotype as a potential contributor to offspring risk of neurodevelopmental phenotypes. For example, the prenatal impact of maternal genotype in 5-HT 1A receptor null mice confers life-long anxiety-like behavior in offspring, independent of offspring genotype (Gleason et al, 2010). This possibility has recently been explored in ASD, with risk increased in the offspring of mothers with the high-expressing SLC6A4 5-HTTLPR long allele (Kistner-Griffin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…44 Although further improvements are required, the intranasal route offers a first potential way for C-1A-siRNA delivery to brain. This route allowed the same effects than the i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…Both C57BL Wild type (WT) and C57BL 5-HT 1A -R (À/À) (KO) female mice were used in this study (Bailey and Toth, 2004;Gleason et al, 2010;Parks et al, 1998;Sarnyai et al, 2000). Mice were acquired, cared for and handled in conformity with the U.S. Public Health Service's ''Guide for the Care and Use of Laboratory Animals''.…”
Section: Animals and Animal Carementioning
confidence: 99%